The equitable reach of a universal, multisector childhood obesity prevention program (Live Life Well @ School) in Australian primary schools - Andrea Bravo; Bridget C Foley; Christine Innes-Hughes; Blythe J O'Hara; Bronwyn McGill; Chris Rissel (Sax Institute, 2020)
Objective: The Live Life Well @ School program aims to establish, reinforce and support primary school students (aged 5-11 years) and their families to adopt healthy eating and physical activity behaviours through the implementation of an evidence-based program that focuses on the school curriculum, the school food and physical activity environment, and teacher professional development. This paper examines Live Life Well @ School monitoring data to provide practical insights into program adoption and changes in primary school environments across NSW, particularly in schools characterised as disadvantaged. Type of program: The Live Life Well @ School program provides a universally delivered, state-wide approach to childhood obesity prevention in the primary school setting. The program is a joint initiative between health and education sector agencies. Methods: The program includes health promotion strategies for primary schools relating to physical activity and nutrition. Adoption of the program is indicated by achievement of evidence-based desirable practices, which are monitored routinely by local health promotion staff using a purpose-built online Population Health Information Management System. Monitoring data are used to provide feedback to schools and identify a staged approach to achieving more desirable practices. Health promotion staff tailor support locally to suit school and community needs, and have additional funding to support socio-economically disadvantaged schools. Results: The program has achieved high reach to schools (82.7% of the 2570 schools in New South Wales, Australia). Adoption of desirable practices within schools participating in 2017 was 72.9%. Equitable reach was achieved for schools in areas of socio-economic disadvantage, schools in remote areas and schools with a high propotion of Aboriginal students, who are likely to have higher rates of childhood overweight and obesity. Curriculum-based strategies were more frequently adopted; environmental changes and teacher professional development components were less well adopted. Lessons learnt: The desirable practice approach allows health promotion officers to tailor support by building on school strengths and taking a staged approach to change. Ongoing monitoring of the program provides useful insights that inform quality improvements to the program and implementation process, as well as information on progress towards outcomes. State-wide program targets were adjusted to strengthen impact and focus on desirable practices that were less well achieved. Intentional targeting and tailoring in areas of disadvantage are required to achieve equitable adoption of such a universal health promotion program. Strong relationships at the local level between school champions (teachers and principals) and health promotion staff characterise success.